Koordinative Schwelle - kritische Geschwindigkeit zwischen Regelkonformitat und Disqualifikation im sportlichen Gehen - Neumann, H. F. (Leipziger Sportwissenschaftliche Beiträge, 2005)
According to the international competition rules race walkers have to keep contact to the ground and knee straightened. To investigate the influence of speed keeping the rules 8 race walkers realized a test on a treadmill. Dependent on speed the coordination changed from correct walking technique to incorrect walking technique and afterwards to running. Incorrect walking begins with occurrence of flight time and bending knee dependent on performance level between speeds of 2,75 to 4,0 m/s. The investigations show a linear function of speed and flight time, however a nonlinear function between speed and knee straightening. To mark the maximum increase of knee straightening in course of speed the term of "coordinative threshold" is introduced.